Ether lipids, sphingolipids and toxic 1‐deoxyceramides as hallmarks for lean and obese type 2 diabetic patients. (14th January 2021) - Hannich, J. Thomas; Loizides‐Mangold, Ursula; Sinturel, Flore; Harayama, Takeshi; Vandereycken, Bart; Saini, Camille; Gosselin, Pauline; Brulhart‐Meynet, Marie‐Claude; Robert, Maud; Chanon, Stephanie; Durand, Christine; Paz Montoya, Jonathan; et al.
Abstract: Aim: The worldwide increase in obesity and type 2 diabetes (T2D) represents a major health challenge. Chronically altered lipids induced by obesity further promote the development of T2D, and the accumulation of toxic lipid metabolites in serum and peripheral organs may contribute to the diabetic phenotype. Methods: To better understand the complex metabolic pattern of lean and obese T2D and non‐T2D individuals, we analysed the lipid profile of human serum, skeletal muscle and visceral adipose tissue of two cohorts by systematic mass spectrometry‐based lipid analysis. Results: Lipid homeostasis was strongly altered in a disease‐ and tissue‐specific manner, allowing us to define T2D signatures associated with obesity from those that were obesity independent. Lipid changes encompassed lyso‐, diacyl‐ and ether‐phospholipids. Moreover, strong changes in sphingolipids included cytotoxic 1‐deoxyceramide accumulation in a disease‐specific manner in serum and visceral adipose tissue. The high amounts of non‐canonical 1‐deoxyceramide present in human adipose tissue most likely come from cell‐autonomous synthesis because 1‐deoxyceramide production increased upon differentiation to adipocytes in mouse cell culture experiments. Conclusion: Taken together, the observed lipidome changes in obesity and T2D will facilitate the identification of T2D patient subgroups and represent an important step towards personalized medicine in diabetes.